Caracterização e eficiência agronômica de fertilizantes organominerais fosfatados sólidos no desenvolvimento inicial do milho (Zea mays) - Lima, Rodrigo Sakurada (2015)
Phosphorus (P) is the most limiting nutrient production in tropical regions soils. This feature stems from the high capacity that these soils have to fix the P, so that gets unavailable to the plants absorbs it. Thus, the increased efficiency of phosphate fertilizers, the use of alternative sources to the minerals and the proper management are important tools to minimize this problem. Therefore, this study aimed to characterize and to evaluate the agronomic efficiency and the residual effect of solid organomineral phosphate fertilizers in the initial development of maize (Zea mays L.) when cultivated with different NPK formulated fertilizers (5-20-2 granulated organomineral - OG, 3-15-2 mixture of granules organomineral - OM and 3-15-2 mixture of granules mineral - MM) and P levels in an Oxisol. For the characterization, physical and chemical fertilizer analyzes were performed for determination of pH, the content of N, K2O, Ca, Mg, S, Fe, Cu, Zn, Mn, carbon, humic acid and fulvic. The P2O5 content determined were the total, soluble in water, in neutral ammonium citrate (CNA) and in citric acid. The fertilizers were further characterized for the particle size, moisture and Fourier Transform Infrared Spectroscopy (FTIR). The experiment was conducted in a greenhouse using pots with 5 kg of soil. Sachets containing OG, OM and MM fertilizers with doses of 0, 25, 50, 100 and 200 mg kg-1 of P were buried in the soil. The amount of fertilizer for each dose was defined according to the total P level found in the characterization. There were performed 4 successive cultivations in the same pot being conducted two corn plants per pot. After 35 days the plants were evaluated, cut and prepared for analysis of levels of P, N, K, Ca and Mg in the dry mass of shoot (MSPA). The three analyzed fertilizers are not in accordance with the IN 25/2009 and the IN 05/2007, which establish standards for the physical and chemical specifications and guarantees necessary and mandatory for fertilizers. The three fertilizers presented the P soluble in water value very similar, although the P soluble in CNA + WATER among them has proved different. By means of FTIR analysis, it was observed the presence of organic aliphatic compounds, protein, lipid, although these have not been quantified. The biometric data and P contents in the MSPA to different doses of P and fertilizers showed quadratic settings initially, but over the cultivations, it have shown linear trends. The MM fertilizer was superior to the OG and OM due to its higher accumulated MSPA. The SPAD index showed similar behavior to the P content in the MSPA, showing that there was response to different doses of P, so that SPAD values were higher when the plants had better development. In the sum of the four cultivations, plants fertilized with OM and MM did not differ and showed higher P accumulated and P Recovery Index in relation to OG. In general, it was observed that OM fertilizer showed better performance than OG, except in the first cultivation.